Pengaruh Financial Distress, Kompensasi Rugi Fiskal, dan Insentif Eksekutif terhadap Tax Avoidance (Studi Empiris pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2019–2023) - Yanti, Sesi Yuni; Sugiyarti, Listya (Worksheet : Jurnal Akuntansi, 2025)
This study aims to analyze the effect of Financial Distress, Fiscal Loss Compensation and Executive Incentives on Tax Avoidance in Property and Real Estate Sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The sampling method used in this study uses the purposive sampling method, with a quantitative research type. The data used is secondary data, namely the company's annual financial report. The number of samples used in this study was 13 Property and Real Estate sector companies with observations for 5 (five) years, so that 65 observations were selected in the form of financial reports. The analysis used is panel data regression analysis using a fixed effect regression model with the EViews version 13 application tool. The results of the study show that simultaneously Financial Distress, Fiscal Loss Compensation and Executive Incentives have an effect on Tax Avoidance and partially Financial Distress has no effect on Tax Avoidance, Fiscal Loss Compensation has no effect on Tax Avoidance, and Effective Incentives has an effect on Tax Avoidance.